A supplement of the genus Diaphanogryllacris (Orthoptera: Gryllacridinae) from China - Du, Baojie; Bian, Xun; Shi, Fuming (Zootaxa, 2016)
Based on the earlier studies (Karny, 1937; Bey-Bienko, 1957; Bey-Bienko & Andrianova, 1959; Di et al., 2014; Liu, 1999; Gorochov & Woznessenskij, 2000; Otte, 2000), Gorochov et al. (2015) reported 4 new species and 3 new subspecies from Thailand and Laos, and Du et al. (2016) described 2 new species from China. So far, the genus Diaphanogryllacris includes 26 species (Eades et al., 2016), 5 of which are recorded in China. This paper is a continuation studies for the Chinese Diaphanogryllacris.